(untitled) (American Journal of Islam and Society, 2004)
Books Reviewed: Why I Am Not a Muslim. New York: Prometheus Books, 2003; The Quest for the Historical Muhammad. New York: Prometheus Books, 2000; What the Koran Really Says: Language, Text, and Commentary. New York: Prometheus Books, 2002; Leaving Islam: Apostates Speak Out. New York: Prometheus Books, 2003. Among other consequences of the horrific tragedy of 9/11 is the generation of a veritable cottage industry in books about Islam and Muslims. There had always existed a void regarding such books. In spite of its Abrahamic roots and its long, if somewhat troubled, encounters with the West, the significance of Arab countries in terms of western economic interests and the steady growth of diasporic Muslims settling in the developed world (easily surpassing the Jewish presence, probably even in the United States), Islam had remained a residual category entirely peripheral to American intellectual or cultural life. The unprecedented nature and the brutality of the event that led to the Muslim “explosion” into the public consciousness exposed the woeful indifference about Islam and reinforced the Orientalist stereotypes of Muslims as mysterious, backward, and menacing. There was a predictable appetite among the public to know about Muslims, who had traditionally been pictured as quaint and dreadful “others” but were now increasingly being presented as angry and threatening “fanatics.” Some of the books rushed to print were works of genuine scholarship, demonstrating experience, knowledge, and elegance. Others were obviously driven by commercial considerations rather than academic, and some were, indeed, shallow, trite, and often misleading. In the latter genre, two classes of books, both critical of Islam, quickly became popular: those written from an alarmist western perspective by such authors as Steven Emerson, Daniel Pipes, and Robert Spencer, and others that were supposedly “insider” exposés and interrogations issuing from such critics as Irshad Manji, the brothers Irgun Mehmet and Emir Fathi Caner, and Mohammad Mohaddessin. The doyen of the latter group is, undoubtedly, Ibn Warraq ...